Changes of resistance, work function and Fermi level during the hydriding of Zr and Sc at 295K - Kandasamy, K.; Surplice, N.A. (My University, 1985)
The turning points on the curve of resistance versus atomic ratio ( gamma =H/Me) were correlated with the phase boundaries of the H/Zr and H/Sc systems at 295K. The changes of work function with r showed that, at low value of r, some H atoms adsorbed on the surface and increased the work function slightly for Zr but decreased it for Sc. They also showed that for H/Zr the Fermi level mu of the FCC hydride was 0.2 eV higher than mu of the FCT hydride and at least 0.07 eV higher than mu of the clean metal. However, mu for Sc was about 0.2 eV higher than mu of its (FCC) hydride.